(3GdfXQjI GdYGeI ddJOQjH aj GdhXjaI GdYGeI (B:s (3OQGSI JWHjbjI ddJOQjH aj eUQ (B/ s - (3GdSjO eMeO jhSa GdeYOGhjs; (3YHO GdMejO MTjTs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3JHOC gPg GdQSGdI HaUd JegjOj Yf GdJYQja HGdJOQjH hCfhGYg, Ke JfbSe Edi bSejf; MjK jCJj GdbSe GdChd Yf GdCYOGO hGdJOQjH GdSGHb Ydi GdGdJMGb HGdhXjaI GdYGeI, Ke GdbSe GdKGfj Yf GdJOQjH HYO GdGdJMGb HGdhXjaI GdYGeI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1978.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI UaMGJ (B467 - 489.s
Keywords: (3GdbGfhf GdEOGQjs; (3GdGdJMGb HGdhXjaI GdYGeIs; (3GdeSGhGI aj JbdO GdhXGFas; (3fXGe egfjI GdhXjaI GdYGeIs; (3Ohd ChQhHG GdZQHjIs; (3fXGe GdJhXas; (3GdJOQjH GddGMbs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs